Shedding Light on the Phytochemical and Biological Fingerprints of Fibigia clypeata (L.) Medik Essential Oil as a Pharmacotherapeutic Agent - Unver, Tuba; Bingul, Murat; Uslu, Harun; Gurhan, Ismet; Goktas, Bunyamin; Sahin, Hasan; Boga, Mehmet (Wiley, 2025)
Since plant essential oil contains medicinally valuable compounds, its usability as a pharmacotherapeutic agent has been the focus of attention within the century's needs. The lack of sufficient studies on the medical and pharmacological evaluation of Fibigia clypeata (L.) Medik has made this plant the target of our study. This study analyzes the phytochemical composition and biological activity of F. clypeata essential oil. As a result, dimethyl disulfide and dimethyl trisulfide were found to be the main compounds of the plant essential oil, with rates of 73.13% and 19.87%, respectively. The antifungal property of plant essential oil is more effective than its antibacterial property, with MIC values ranging between 0.039 and 0.312 mu L/mL for fungal species and up to 3.750 mu L/mL for bacterial species. The enzyme inhibition profiles were investigated towards two enzymes, namely, anticholinesterase and alpha-glucosidase, targeted for anti-diabetic studies. Anticholinesterase activity was proved with the IC50 values of 17.31 and 4.78 mu g/mL for Acetylcholinesterase (AChE) and Butyrylcholinesterase (BChE) enzymes, respectively. DPPH and CUPRAC activities were the most promising antioxidant studies, with values of 1.54 and 3.72 mu g/mL. It was observed that alpha-Terpineol made a hydrogen bond with ASN80, and 1-(2,6,6-Trimethyl-1,3-cyclohexadien-1-yl)ethanol made a hydrogen bond with SER82. Although molecular dock scores were better for antifungal activity, it was determined that no interactions, such as hydrogen bonding or pi interaction, were observed. This preliminary study showed that F. clypeata essential oil is a natural source with promising in vitro antimicrobial, antioxidant, and anticholinesterase activities that warrants further investigation, including safety assessments, due to the high concentration of sulfur-containing compounds. Molecular docking and ADME prediction results showed that alpha-Terpineol and 1-(2,6,6-Trimethyl-1,3-cyclohexadien-1-yl)ethanol were more prone to antimicrobial activity.
Keywords: ADME predictions; anticholinesterase activity; antimicrobial agents; antioxidants; dimethyl disulfide; dimethyl trisulfide; Fibigia clypeata; molecular docking